Widefield heterodyne interferometry using a custom CMOS modulated light camera - Patel, Rikesh; Achamfuo-Yeboah, Samuel; Light, Roger; Clark, Matt (Optical Society of America, 2011)
In this paper a method of taking widefield heterodyne inter- ferograms using a prototype modulated light camera is described. This custom CMOS modulated light camera (MLC) uses analogue quadrature demodulation at each pixel to output the phase and amplitude of the modu- lated light as DC voltages. The heterodyne interference fringe patterns are generated using an acousto-optical frequency shifter (AOFS) in an arm of a Mach-Zehnder interferometer. Widefield images of fringe patterns acquired using the prototype MLC are presented. The phase can be measured to an accuracy of ±6.6◦. The added value of this method to acquire widefield images are discussed along with the advantages.